(3GdeNJGQ ddaJhis - (3GdehUdj, CHh GdaVd, YHO Gddg Hf eMehO Hf ehOhO, J (B683 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eLO GdOjf eMehO Hf ehOhO Hf eMehO Hf HdOLj Cf CLeY eNJUQG Ydi ePgH CHj MfjaI aLeYJ dg gPG GdeNJUQ hSejJg GdeNJGQ ddaJhi cJGH GdWgGQI ef CQGO GdUdhIs
(3BNQgG (B:s
- (3bGd dZjQg Wdb GeQCJj hdh bGd dg Ef TFJ JbjO HGdeLdS hdh bGd dgG Wdbj faSc cdgG TFJ adgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 135s
(3eYLe GdeDdajf (B2 / 295s
(3cTa GdXfhf (B2 / 1622s
(3gOjI GdYGQajf (B1 / 462s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs